Attachment Theory and the Doctrine of Adoption: Making the Connections - Davis, John Jefferson (Journal of psychology and theology, 2025)
This article attempts new integration of attachment theory and the biblical doctrine of adoption, by proposing connections that (1) illuminate the affective dimensions of the doctrine of adoption, and that (2) provide theological resources for pastoral and clinical practices intended to mitigate negative effects of insecure maternal–infant attachments. Overviews of key aspects of the biblical doctrine of adoption and of attachment theory are presented, together with biblical justifications for attempting to integrate them for pastoral and clinical practice. The affective elements of the doctrine of adoption are highlighted in light of attachment theory, and meditation on biblical texts portraying God as benevolent and firmly attached is presented as a means of mitigating lingering negative effects of insecure maternal-infant attachments. Suggestions for further research are offered.